2015
DOI: 10.1155/2015/792578
|View full text |Cite
|
Sign up to set email alerts
|

Acute Necrotizing Encephalopathy: An Underrecognized Clinicoradiologic Disorder

Abstract: Acute necrotizing encephalopathy (ANE) is a rare but distinctive type of acute encephalopathy with global distribution. Occurrence of ANE is usually preceded by a virus-associated febrile illness and ensued by rapid deterioration. However, the causal relationship between viral infections and ANE and the exact pathogenesis of ANE remain unclear; both environmental and host factors might be involved. Most cases of ANE are sporadic and nonrecurrent, namely, isolated or sporadic ANE; however, few cases are recurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
290
0
20

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(321 citation statements)
references
References 70 publications
11
290
0
20
Order By: Relevance
“…A composite scoring system was devised for patients with ANEC by Wong et al 21 who observed a positive correlation between the MRI brain findings and clinical outcome. Follow-up imaging in survivors had shown significant regression of lesions with residual changes like cortical atrophy, cystic changes and haemosiderin deposition 12. Follow-up imaging in our patient had shown significant resolution of signal abnormalities with persistent cytotoxic oedema in the bilateral thalami and previous reports have rarely described persistent inflammation in the follow-up imaging, which might explain the incomplete recovery.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…A composite scoring system was devised for patients with ANEC by Wong et al 21 who observed a positive correlation between the MRI brain findings and clinical outcome. Follow-up imaging in survivors had shown significant regression of lesions with residual changes like cortical atrophy, cystic changes and haemosiderin deposition 12. Follow-up imaging in our patient had shown significant resolution of signal abnormalities with persistent cytotoxic oedema in the bilateral thalami and previous reports have rarely described persistent inflammation in the follow-up imaging, which might explain the incomplete recovery.…”
Section: Discussionsupporting
confidence: 61%
“…It is speculated that following a viral infection, there is an increase in the inflammatory mediators such as interleukin-1, interleukin-6 and tumour necrosis factor α 13. A cytokine storm following viral infection leading to systemic immune response could possibly explain the pathogenesis and clinical presentation in patients with ANEC 12 14. Although CSF PCR for H1N1 influenza was not performed in our case, a previous observation of rare isolation of the influenza virus from CSF has supported the hypothesis that ANEC reflects a cytokine storm mediated central nervous system injury 15.…”
Section: Discussionmentioning
confidence: 99%
“…Other symptoms include fever, vomiting, and respiratory symptoms [11]. As mentioned before, it is generally considered to be a post-infectious disease secondary to immune mediated response which is triggered by the virus [12]. Although ANE may affect adults, most cases of ANE reported in the literature are usually children [13].…”
Section: Discussionmentioning
confidence: 99%
“…Neuroimaging usually demonstrates multifocal bilateral periventricular white matter, thalamic, brain stem, or cerebellar changes [16]. On pathology, affected areas of the brain are characterized by the presence of hemorrhages and necrosis [12]. ANE carries a bad prognosis and patients usually end up with either profound disability or death [17].…”
Section: Discussionmentioning
confidence: 99%
“…There is an association with upper respiratory tract illnesses, particularly influenza A 2 3. It has significant morbidity and mortality 4 5. Evidence regarding optimal therapy is limited; however, early steroids and immunoglobulin is associated with improved outcome 5.…”
mentioning
confidence: 99%